Synthesis of disaccharide modified berberine derivatives and their anti-diabetic investigation in zebrafish using a fluorescence-based technology. Issue 18 (29th April 2020) - Wang, Lizhen; Kong, Haotian; Jin, Meng; Li, Xiaobin; Stoika, Rostyslav; Lin, Houwen; Liu, Kechun
Abstract : Diglucose modified berberine derivatives can dramatically promote the uptake of 2-NBDG in both zebrafish larvae and their eyes. Abstract : Berberine is a naturally occurring isoquinoline alkaloid and has been used as an important functional food additive in China due to its various pharmacological activities. Berberine exhibits great potential for developing anti-diabetic agents against type 2 diabetes mellitus (T2DM), as it can reduce the blood glucose level in many animal models. However, the low anti-diabetic activity and poor bioavailability of berberine (below 5%) by oral administration significantly limit its practical applications. To solve these problems, this article focuses on the structural modification of berberine using some disaccharide groups, because the carbohydrate moiety has been proved to improve the bioavailability and enhance the receptor-binding affinity of drugs. Anti-diabetic investigation of the synthesized compounds was performed in a zebrafish model using a fluorescently labelled glucose analog 2-deoxy-2-[(7-nitro-2, 1, 3-benzoxadiazol-4-yl)amino]-d -glucose (2-NBDG) as a glucose tracker. The results indicated that the modification of berberine with carbohydrate groups could give derivatives with improved anti-diabetic activity, in particular the diglucose modified berberine derivative 1 which could dramatically promote the uptake of 2-NBDG in both zebrafish larvae and their eyes even at very low concentrations. Furthermore, the fluorescence-based anti-diabetic investigation method in zebrafish shows great potential for anti-diabetic drug screening.